Growing Up with Mies and Saarinen - Paul Guyer; Laure van Heijenoort (Aesthetic Investigations, 2023)
Paul Guyer interviews his cousin Laure van Heijenoort, who as a teenager lived for several years with her parents in one of Mies van der Rohe's Lafayette Park townhouses in Detroit and attended school at Eliel Saarinen's Cranbrook campus.  She reports on her experiences of living and study in both, experiences still vivid to her and now to a broader audience.